Predicting Readmission and Leak Rates Following Colectomy with Red Cell Distribution Width: A Simple but Effective Test - Kyle G Cologne; Loriel Liwanag; Bikash Devaraj; Elizabeth Arcila; Glenn T Ault; Adrian E Ortega; Anthony J Senagore (Global Journal of Perioperative Medicine - Peertechz Publications, 2017)
Introduction: Prediction of readmission as a result of either delayed presentation of infection, or worse an anastomotic leak is difficult. Efficient reduction in the length of stay and being able to predict problematic patients who may be readmitted or develop complications would be advantageous. To date, other tests including CRP have proven to be insufficiently sensitive for this task. Materials & Methods: We performed a single center, retrospective review of patients admitted to a large, urban safety net hospital who underwent colectomy over a two year period to determine the predictive value of red cell distribution width (RDW) on the development of anastomotic leak or readmission within 30 days following hospital discharge. Results: A total of 118 patients underwent colectomy during this period. Readmission and/or anastomotic leak occurred in 49 patients. The sensitivity of elevated RDW levels (greater than or equal to 14.0) at detecting future readmission and/or leak was 89.8%. The negative predictive value for a normalized RDW below 14.0 at predicting the non-occurrence of leak or readmission was 87.7%. The specificity of an elevated RDW was 72.4% and the positive predictive value was 76.5%.